2021
DOI: 10.1155/2021/5585676
|View full text |Cite|
|
Sign up to set email alerts
|

MRI Manifestations and Diagnostic Value of Chronic Osteomyelitis

Abstract: If chronic osteomyelitis is not treated promptly and thoroughly, the wound will not heal for a long time, and the affected limb will be dysfunctional or disabled. In severe cases, it may even require amputation. In this article, a total of 50 patients with chronic osteomyelitis who meet the inclusion criteria were selected from January 2019 to March 2020 and were divided into two groups based on patient compliance, namely, a treatment group and a control group. The results of this group of studies showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The results of the analysis of this single-center study with 75 consecutive cases of confirmed extremity OM demonstrate that none of the imaging characteristics assessed on MR or XR modalities are predictive of a patient's outcomes and midterm survival rates. Although studies have shown that MR is a more accurate modality for diagnosing and determining the extent of OM, 15–18 our hypothesis of predictive capability of imaging findings for patient outcomes was refuted. Radiographs, although routinely used as the initial imaging modality for OM, also exhibited no significant predictive value for prognostication of OM-related outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…The results of the analysis of this single-center study with 75 consecutive cases of confirmed extremity OM demonstrate that none of the imaging characteristics assessed on MR or XR modalities are predictive of a patient's outcomes and midterm survival rates. Although studies have shown that MR is a more accurate modality for diagnosing and determining the extent of OM, 15–18 our hypothesis of predictive capability of imaging findings for patient outcomes was refuted. Radiographs, although routinely used as the initial imaging modality for OM, also exhibited no significant predictive value for prognostication of OM-related outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, ultrasonography was an upcoming promising screening tool as it has the ability to show acute findings of extraosseous pathology and/or periosteal elevation in osteomyelitis at an earlier stage [ 8 ]. MRI is the imaging modality of choice for the diagnosis of osteomyelitis and shows marrow edema typically presents as a localized marrow abnormality of decreased signal on T1-weighted images and increased signal on T2-weighted images [ 9 ]. The most acute finding of osteomyelitis on MRI is bone marrow edema or indirect findings of osteomyelitis such as soft-tissue collections, cellulitis, and cortical bone sinus tracts.…”
Section: Discussionmentioning
confidence: 99%
“…The bone scan is useful in multifocal diseases in particular, because easy to scan the whole body. However, the gold standard tool remains tissue biopsy and culture [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%